2010
DOI: 10.1248/cpb.58.94
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antitumor Evaluation and Crystal Structure of Hydroxyurea Derivatives

Abstract: Hydroxyurea (HU) has been used in cancer chemotherapy for many years. It has been of manifold pharmacological interest, so it has been used for the treatment of melanoma, chronic myelocytic leukemia, and recurrent, metastatic, or inoperable ovarian cancer. HU is also used in therapy of squamous cell carcinomas in the head and neck and relapsed metastasis ovarian cancer, 1) and people have found that it has certain effect on sickle cell anemia, 2) beta-thalassemia, 3) and psoriasis.4) It is also reported that H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The synthesis started from commercially available hydroxyurea 5 which was O -benzylated with BnBr in the presence of KOH under reflux to provide 1-(benzyloxy)urea 6 in high yield. 29 Cyclocondensation of 1-(benzyloxy)urea 2 and diethyl malonate provided six-membered heterocycle compound 3-(benzyloxy)-6-hydroxypyrimidine-2,4(1H,3H)-dione 7 in moderate yield under microwave irradiation (150 °C, 20 min) or under conventional heating (reflux, overnight). 30 Compound 7 was converted to key intermediate 3-(benzyloxy)-6-chloropyrimidine-2,4(1H,3H)-dione 8 by reacting with POCl 3 in the presence of BnEt 3 NCl.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis started from commercially available hydroxyurea 5 which was O -benzylated with BnBr in the presence of KOH under reflux to provide 1-(benzyloxy)urea 6 in high yield. 29 Cyclocondensation of 1-(benzyloxy)urea 2 and diethyl malonate provided six-membered heterocycle compound 3-(benzyloxy)-6-hydroxypyrimidine-2,4(1H,3H)-dione 7 in moderate yield under microwave irradiation (150 °C, 20 min) or under conventional heating (reflux, overnight). 30 Compound 7 was converted to key intermediate 3-(benzyloxy)-6-chloropyrimidine-2,4(1H,3H)-dione 8 by reacting with POCl 3 in the presence of BnEt 3 NCl.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of cell-proliferation was measured by the improved MTT assay. 6,24) The inhibitory potency (IC 50 ) of tested compounds are given in Table 1. In general, some target compounds showed good inhibitory effects on L1210 and K562, especially 4a, 4b, 4d, 4e, 4g, 4q, 4c′ and 4f′.…”
Section: Resultsmentioning
confidence: 99%
“…9,[15][16][17][18] In previous paper, we reported HU monosubstituents and disubstituents with benzyls at N-positions of HU. 6,19) The results indicated that the stronger hydrophobic nature of the HU derivatives might favor the cytotoxic activity and benzyl groups at the N-position of HU were associated with enhanced cytotoxic activity. The disadvantages associated with HU's physicochemical properties, e.g., very high hydrophilicity (log P: −1.80) and small molecular size, may be overcomed by the structural modification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After culturing for 12 h at 37°C and 5% CO 2 , cells were incubated with samples for 24 h using five concentrations at 10-fold dilutions (10 -3 -10 -7 mol/ml) for each test compound. MTT was added at a terminal concentration of 5 lg/ml and incubated with the cells for 4 h. The formazan crystals were dissolved in DMSO (100 ll) in each well and the optical density was measured at 570 nm (for the absorbance of MTT formazan) (Mai et al, 2010). The IC 50 was calculated using the Bacus Laboratories Incorporated Slide Scanner (Bliss) software.…”
Section: In Vitro Cytotoxicity Screeningmentioning
confidence: 99%